2015 ESC GUIDELINES FOR THE MANAGEMENT OF INFECTIVE ENDOCARDITIS - Gilbert Habib; Patrizio Lancellotti; Manuel J. Antunes; Maria Grazia Bongiorni; Jean-Paul Casalta; Francesco Del Zotti; Raluca Dulgheru; Gebrine El Khoury; Paola Anna Erba; Bernard Iung; Jose M. Miro; Barbara J. Mulder; et al. (Российский кардиологический журнал)
The Task Force for the Management of Infective Endocarditis of the European Society of Cardiology (ESC)Endorsed by: European Association for Cardio-Thoracic Surgery (EACTS), the European Association of Nuclear Medicine (EANM)